HARD PALATE DEVELOPMENT AND STRUCTURE FORMING IN THE FIRST TRIMESTER OF THE INTRAUTERINE DEVELOPMENT PERIOD - Prodanchuk, A.I. (World of Medicine and Biology, 2018)
Peculiarities of certain formations structure in the mouth area, hard palate in particular, of syntopy and structure transformation are still topical issues for morphologists and clinicians. The investigation aim was to reveal peculiarities of hard palate development and structure forming in human embryos and pre-fetuses. Human 14 embryos and 19 pre-fetuses have been investigated with macroscopy, microscopy series of sequential topographic-anatomic sections, of conventional and thin preparations. It was established, that in embryos 12.0 – 13.0 mm ТDC Trans Cranial Dopplerography (6-7 weeks) the posterior department of nasal chambers is separated from the initial mouth cavity by a small plate - nasal-mouth membrane. The process of nasal chambers breakthrough into the initial mouth cavity is observed, the result of which is connection occurrence between initial nasal and mouth cavities. They are divided by the primordium of initial primitive palate, which thickness at this development stage is 270±30 mcm, width is 1150±70 mcm, and length is 280±40 mcm. By the end of 8th week of intrauterine development palatine processes move from oblique (almost vertical) to horizontal position. In the 10th week (42.0-53.0 mm ТDC) complete fusion of palatine processes in the front is observed, except small clusters of epithelial “plugs” – ingrowths of the stratified epithelium to adjacent connective tissue along the midline. An availability of epithelial plug in the nasal cavity creates morphologic preconditions of hard palate horizontal position. By the end of pre-fetus period hard palate obtains definitive structure and is presented by palatine processes of maxilla anlage and horizontal plate of palatine bone anlage. The transversal size of the palate is 3500±70 mcm, anterior-posterior one is 8000±130 mcm.